Monster mayhem - Eliopoulos, Chris, 1983- (Dial Books for Young Readers, 2020)
Zoe loves two things: science and monster movies. After finding a mysterious ring, she puts it on and is enveloped by a burst of light. When she wakes up in the morning, a monster from one of her favorite movies is at her window--and she is in for an adventure!